1991
DOI: 10.1117/12.43995
|View full text |Cite
|
Sign up to set email alerts
|

Caries selective ablation by pulsed lasers

Abstract: The aim of the study was to fmd conditions for selective ablation of carious dentine. Absorption characteristics of healthy enamel, dentine, and carious lesions were studied by means of microspectrophotometry. It was found that in the spectral range of 330 to 520 nm optical density of carious dentine is higher by about a factor of 4 as in respect to healthy dentine. In the second part of the study ablation thresholds were studied for different tissues at 355 nm (frequency tripled Q-switched Nd:YAG-Laser). By m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0
1

Year Published

1995
1995
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 1 publication
0
7
0
1
Order By: Relevance
“…10 Extensive in vitro research has been performed to remove carious tissue in the NUV using a frequency-doubled alexandrite laser (λ = 377 nm). 11,12 Carious dentin is removed at 11.7 μm/pulse, whereas healthy dentin is removed at 0.2 μm/pulse at a fluence of 4 J/cm 2 . 12 (Fluence is also called energy-flux density and energy density with units of energy per unit area.)…”
Section: Introductionmentioning
confidence: 99%
“…10 Extensive in vitro research has been performed to remove carious tissue in the NUV using a frequency-doubled alexandrite laser (λ = 377 nm). 11,12 Carious dentin is removed at 11.7 μm/pulse, whereas healthy dentin is removed at 0.2 μm/pulse at a fluence of 4 J/cm 2 . 12 (Fluence is also called energy-flux density and energy density with units of energy per unit area.)…”
Section: Introductionmentioning
confidence: 99%
“…This concept has been clearly demonstrated on enamel using 355-nm, 377-nm, and 1064-nm Nd:YAG laser pulses with without an added absorber. Rechmann and Hennig have shown that near-UV photons of ns-duration are well suited for the selective removal of caries and dental calculus at relatively low incident fluence [1][2][3][4][5]. At the longer laser wavelengths, namely 1064 and 532-nm, markedly higher single pulse energies are required for ablation and there is deep penetration of the laser light which poses a risk to underlying tissue [6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…This concept has been clearly demonstrated on enamel using 355-nm, 377-nm, and 1064-nm Nd:YAG laser pulses with or without an added absorber fluence 1-8 . Rechmann and Hennig have shown that near-UV photons of ns-duration are well suited for the selective removal of caries and dental calculus at relatively low incident fluence [1][2][3][4] . At the longer laser wavelengths, namely 1064 and 532-nm, markedly higher single pulse energies are required for ablation and there is deep penetration of the laser light which poses a risk to underlying tissue and the pulp [5][6][7][8] .…”
Section: Introductionmentioning
confidence: 99%